The Impact of Intestinal Parasitic Infections on the Nutritional Status of Rural and Urban School-Aged Children in Nigeria - Kenneth N. Opara, PhD; Nsima I. Udoidung, PhD; Dominic C. Opara, PhD; Okpok E. Okon, PhD; Evelyn E. Edosomwan, PhD; Anietie J. Udoh, BSc (Global Health and Education Projects, Inc., 2012)
Objectives:Intestinal parasitic infection and undernutrition are still major public health problems in poor and developing countries. The objective of this study was to assess the relationship between intestinal parasitic infection and nutritional status in 405 primary school children from rural and urban areas of Akwa Ibom State, Nigeria.Methods:This cross-sectional survey in 2009 obtained anthropometric data, height-for-age (HA), weight-for-height (WH) and weight-for-age (WA) Z-scores from each child and fecal samples were also collected and screened for intestinal parasites using standard parasitological protocols.Results:The prevalence of infection with any intestinal parasite was 67.4%. A total of six intestinal parasites were detected; hookworm (41.7%) had the highest prevalence. The prevalence of intestinal parasites and undernutrition was significantly higher in rural than in urban children (P<0.001). The prevalence of stunting (HAZ < -2), underweight (WAZ < -2) and wasting (WHZ < -2) for rural and urban children were 42.3% vs. 29.7%; underweight 43.2% vs. 29.6% and wasting 10.9% vs. 6.4%, respectively. With respect to nutritional indicators, the infected children had significantly (P<0.05) higher z-scores than the uninfected children. Multivariate logistic regression analysis showed that only Hookworm and Ascaris lumbricoides were each significantly (P<0.05) associated with stunting, wasting, and underweight.Conclusions and Public Health Implications:Since intestinal parasitic infections are associated with malnutrition, controlling these parasites could increase the physical development and well-being of the affected children.